Fabrication and evaluation of chitosan modified filter paper for chlorpyrifos detection in wheat by surface‐enhanced Raman spectroscopy. (20th July 2022) - Aheto, Joshua Harrington; Huang, Xingyi; Wang, Chengquan; Tian, Xiaoyu; Yi, Ren; Yuena, Wang
Abstract: Background: Chlorpyrifos is a commonly used organophosphorus pesticide in agriculture. However, its neurotoxicity poses a huge threat to human health. In the present study, a chitosan‐modified filter paper‐based surface enhanced Raman scattering active substrate (Ch/AgNPs/paper) was fabricated and used to detect trace amounts of chlorpyrifos in 120 treated wheat samples. Results: Results showed that the Ch/AgNPs/paper substrate could be used to enhance the chlorpyrifos spectral fingerprint only up to a concentration of 0.000558 mg L −1 . Following Raman spectra acquisition, three pre‐processing methods, including Savitzky–Golay (Savitsky–Golay filter with a second order polynomial) smoothing with first derivative and second derivative and normalization, were used to reduce baseline variation and increase resolutions of spectral peak features of the original spectra dataset. Then, prediction models based on partial least squares were established for detecting chlorpyrifos pesticide residue in wheat. The partial least squares model with normalization yielded optimal result, with a correlation coefficient of 0.9764, root mean square error of prediction of 1.22 mg L −1 in the prediction, and relative analysis deviation of 4.12. Five unknown samples were prepared to verify the accuracy of the prediction model. The predicted recoveries were calculated to be between 97.25% and 119.38% with an absolute t value of 0.598. The value of a t‐ test shows that the prediction model is accurate and reliable. Conclusion: The present study demonstrates that the proposed method can achieve rapid detection of chlorpyrifos in wheat. © 2022 Society of Chemical Industry.